Analisis Aspek Kepribadian Tokoh Utama Dalam Novel Trauma Karya Boy Candra, Implikasinya Terhadap Pembelajaran Sastra Di SMA - Tiroi Lumbanraja; Alifiah Nurachmana; Patrisia Cuesdeyeni; Linggua Sanjaya Usop; Stefani Ratu Lestariningtyas (Universitas Palangka Raya, 2023)
The purpose of this study is to describe the 3 aspects of personality proposed by Sigmund Freud, namely the id, ego, and superego contained in the main character of Boy Candra's novel Trauma and their implications for learning literature in high school. The method used in this research is descriptive qualitative research method. The data used in this study are quotes that are included in the 3 aspects of personality in Boy Candra's novel Trauma. The results of this study indicate that (1) Id in the main character, Kimara, originates from the instinct of curiosity about what actually happened. (2) The ego in the kimara character always realizes the demands of the id. The ego in the Kimara character always acts as a conveyer of reality, that is, when the instinct of curiosity exists, the ego will always act. (3) Kimara's superego is based on moral values. (4) This research has implications for learning literature in high school, namely analyzing the content and language of the novel, interpreting the author's view of life in the novels they read.